TINJAUAN IMPEMENTASI PENILAIAN KINERJA DI POLMAN BANDUNG - Ariyani, Emma Dwi (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2013)
Human resource management is a process to determine the success of an organization in achieving its goals. One ofthe important functions of human resource management in any organization is its employees performance rating. Performance appraisal allows a company to identify the strengths and weaknesses of its employees, and this allows the opportunity for employees to increase acceptance salaries and promotions. Almostall companies conduct informal and formal measures in assessing the performance of their employees. Performance assessment means evaluating the performance of the employee's current and / or past performance relative to standards. Employees are regularly assessed its performance and use assessment results to make recommendations regarding the status of a worker in the future. These recommendations can be used as consideration to salary adjustments, new tasks, or changes in the structure ofemployment